Linear drives in metal forming machines and peripherals–recent developments. (April 2016) - Behrens, B.-A.; Krimm, R.; Reich, D.; Teichrib, S.
Abstract: In this paper the recent developments in linear motor driven systems in the field of metal forming technology are presented, where an increasing use of linear motors in peripheral devices such as feeders or transfer systems as well as in main press drives could be noticed. Within the presented research projects the manufacturing accuracy and the stroke rate of presses as well as the energy efficiency can be significantly increased by using linear motors.